Sustainable finance disclosure in ASEAN’s banking industry: Do board independence and diversity matter? - Rahayu; Djuminah; Setiawan, Doddy (International Journal of Management and Sustainability, 2024)
This paper aims at investigating the relation between board independence and diversity (gender diversity and nationality diversity) on sustainable finance disclosure (SFD) in ASEAN’s banking industry. We collected the SFD data from the sustainable finance report. The board independence variable is measured using the percentage of independent board members, while the board diversity is measured using Blau’s index. This paper uses data with a total of 276 observations from 2017 to 2019 using two panel data regressions: fixed effect and random effect. The result of the study indicates that the SFD in ASEAN is at a low level because there are only 34 banks that implement SFD. SFD has a positive association with the board’s independence. While the gender diversity on the board is not significantly affecting the SFD. The board’s nationality diversity is negatively associated with SFD. The results of this study can be useful in evaluating the implementation of SFD for each banking organization in Southeast Asia. Furthermore, we expect the results of this research to assist ASEAN financial regulators and banking associations in optimizing SFD as a means of addressing the issue of climate change.